2009
DOI: 10.1002/mus.21544
|View full text |Cite
|
Sign up to set email alerts
|

The 6‐minute walk test as a new outcome measure in Duchenne muscular dystrophy

Abstract: Walking abnormalities are prominent in Duchenne muscular dystrophy (DMD). We modified the 6-minute walk test (6MWT) for use as an outcome measure in patients with DMD and evaluated its performance in 21 ambulatory boys with DMD and 34 healthy boys, ages 4 to 12 years. Boys with DMD were tested twice, approximately 1 week apart; controls were tested once. The groups had similar age, height, and weight. All tests were completed. Boys who fell recovered rapidly from falls without injury. Mean +/- SD [range] 6-min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
317
1
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 347 publications
(341 citation statements)
references
References 39 publications
8
317
1
15
Order By: Relevance
“…The difference in walking variability across studies might be due to different sample sizes, neuromuscular diseases, disease severity and methods. Although the walking distance increased significantly, several patients walked shorter at retest, which is consistent with findings from a study of Duchenne muscular dystrophy [14,15]. This reflects that variability among repeated tests is not only caused by a learning effect, but also unpredictable random effects such as motivation, fatigue, and other day-to-day variations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The difference in walking variability across studies might be due to different sample sizes, neuromuscular diseases, disease severity and methods. Although the walking distance increased significantly, several patients walked shorter at retest, which is consistent with findings from a study of Duchenne muscular dystrophy [14,15]. This reflects that variability among repeated tests is not only caused by a learning effect, but also unpredictable random effects such as motivation, fatigue, and other day-to-day variations.…”
Section: Discussionsupporting
confidence: 89%
“…The distance increased by 4 m in the 2MWT, which is comparable to studies in participants with non-NMDs [5][6][7][8][9], but a learning effect in the 2MWT has never been investigated before in patients with NMDs. The increase of 11 m in the 6MWT from test to retest is a little lower than the 17-24 m reported in other NMD-studies [4][5][6][7][8][9][10][11][12][13][14][15]. The difference in walking variability across studies might be due to different sample sizes, neuromuscular diseases, disease severity and methods.…”
Section: Discussionmentioning
confidence: 70%
“…The overall historical control cohort used was considered a valid comparator group based on the following: (1) all patients who met the predefined entry criteria and visited the participating centers during the enrollment period were included in the historical control studies, supporting that the population enrolled represents an unbiased control cohort of DMD patients; (2) patients with cognitive impairment that could impact 6MWT outcome were excluded from all studies; (3) the participating clinics specialize in neuromuscular care and follow the internationally recognized treatment guidelines for patients with DMD27, 28 that is used for the eteplirsen‐treated patients, including recommendation for corticosteroid use, dose, and dose adjustment; (4) assessments of the 6MWT were performed by specifically trained physiotherapists according to the same established standards used for the eteplirsen‐treated patients 13. To further increase comparability between the groups not only at baseline but also by rate of disease progression, control patients were matched to the eteplirsen population based on (5) corticosteroid use, (6) age, and (7) genotype.…”
Section: Discussionmentioning
confidence: 99%
“…The 6MWT is an ambulatory outcome measure that has been utilized in clinical trials for 3 DMD therapeutics (eteplirsen, drisapersen, and ataluren) and has been shown to be accurate and reproducible 13. Understanding of DMD disease progression as measured by 6MWT has increased in recent years with publications of natural history data14, 15, 16, 17, 18, 19 as well as placebo‐arm reporting from DMD trials 20, 21, 22.…”
mentioning
confidence: 99%
See 1 more Smart Citation